Harga Diri, Sexting dan Jumlah Pasangan Seks yang Dimiliki oleh Pria Lajang Pelaku Perilaku Seks Berisiko - Rahardjo, Wahyu; Saputra, Maizar; Hapsari, Indria (Jurnal Psikologi, 2015)
One of the risky sexual behaviors is the number of sexual partnersindividuals have. The higher number they have is the riskier for them to get infected by HIV/AIDS. The tendency to commit risky sexual behavior is higherin single person and itsaid that mean committing itrisky are more permissive than women. There have been researches studying the contribution of self-esteem to the number of sexual partners. Sexting is also assumed to have a correlation with the numberof sexual partners. The aimof this study was to measure the contribution of self-esteem and sexting to the numberof sexual partners a single heterosexual man withrisky sexual behaviors have. This study involved 83 participants. The result showed that the contribution of self-esteem to the number of sexual partners was 13.8% and sexting was 9.8%while the combination of self-esteem and sexting to the number of sexual partners was13.2%. The other findings indicated that the number of sexual partners varied in the participants based on educational background, while the self-esteem and sexting varied in them based on sexual orientation